2021
DOI: 10.3389/fagro.2021.622367
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Rhizosphere Bulk Density and Mucilage Gradients on Root Water Uptake

Abstract: In models of water flow in soil and roots, differences in the soil hydraulic properties of the rhizosphere and the bulk soil are usually neglected. There is, however, strong experimental evidence that rhizosphere and bulk soil hydraulic properties differ significantly from each other due to various root-soil interaction processes. Two such processes, which can also influence each other, are rhizosphere loosening or compaction and mucilage deposition. In this work, we identified realistic gradients in rhizosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 73 publications
1
21
3
Order By: Relevance
“…Aravena et al (2014) showed that root-induced soil compaction led to an increase in water flow towards the root in a very loose soil (i.e., 1 g cmş). Landl et al (2021) showed that the lower BD around the roots, as observed in our study, had the effect of reducing water flow to the roots. By modeling the coupled effect of rhizosphere BD and mucilage concentration gradients in the rhizosphere at the single root segment scale, they showed that transpiration levels were kept lower during longer times, and that this could be regarded as beneficial since it would prevent fast dehydration.…”
Section: 4supporting
confidence: 77%
See 1 more Smart Citation
“…Aravena et al (2014) showed that root-induced soil compaction led to an increase in water flow towards the root in a very loose soil (i.e., 1 g cmş). Landl et al (2021) showed that the lower BD around the roots, as observed in our study, had the effect of reducing water flow to the roots. By modeling the coupled effect of rhizosphere BD and mucilage concentration gradients in the rhizosphere at the single root segment scale, they showed that transpiration levels were kept lower during longer times, and that this could be regarded as beneficial since it would prevent fast dehydration.…”
Section: 4supporting
confidence: 77%
“…By modeling the coupled effect of rhizosphere BD and mucilage concentration gradients in the rhizosphere at the single root segment scale, they showed that transpiration levels were kept lower during longer times, and that this could be regarded as beneficial since it would prevent fast dehydration. Modeling approaches of water flow should orient towards integrating explicitly the rhizosphere soil structure and to evaluate its effect on soil water dynamics at the plant scale (Landl et al., 2021). Rhizosphere soil structure properties, and how they differ from bulk soil properties, should also be considered for the interpretation of chemical imaging data, the study of diffusive processes such as mucilage exudation, and the assessment of the suitability of the rhizosphere as a habitat for microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The low dihexose intensity in regions furthest away from the root indicates a low level of blank contribution by the sample preparation workflow (see also Supplementary Figure 1 ). The non-linear decrease in intensity can be caused either by microbial utilization ( Fischer et al, 2010 ) or by sorption to minerals or organic matter in the soil ( Kaiser and Guggenberger, 2003 ) but is also expected from diffusive gradients around the roots ( Raynaud, 2010 ; Vetterlein et al, 2020 ; Landl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rizpolozhenskii (summarised with other Russian work by Ackert, 2013) who concluded that soil formation involved the interaction of two primary factors, all living organisms and rock, with "the seizure of food by organisms from the unorganized environment and its reciprocal return" paramount. Soil for Rizpolozhenskii represented "a border between the chaotic environment and the world of order" with state factors such as climate and topography viewed only as external conditions (quotation from Lapenis et al, 2000). This view of soil formation chimes with the recent paleoclimatic and paleosoil research mentioned earlier that demonstrates the key role of roots and their associated microorganisms in rock weathering (Edwards et al, 2015;Mitchell et al, 2021).…”
Section: Water Movement and Filtrationmentioning
confidence: 93%
“…Admittedly, this is a challenging topic but the increasing ability to characterise root system architecture (RSA) in models (e.g., Postma and Black (2021) for crops; Tobin et al (2007) for trees) coupled with the experimental evidence that RSA and root growth patterns affect preferential flow (Cheng et al, 2011) and flood incidence (Macleod et al, 2013) suggests that this could be a worthwhile realm to explore. RSA and rhizosphere properties such as mucilage and bulk density are being incorporated into models of plant water uptake (Daly et al, 2018;Landl et al, 2021), but effects on macropore flow are yet to be included. Hiltner (1904) coined the term rhizosphere to explain his observations that specific processes were occurring at the root/soil interface that was different from those in the bulk soil.…”
Section: Water Movement and Filtrationmentioning
confidence: 99%